Surgical management and outcome of medulloblastoma patients at Addis Ababa between 2010 and 2018 - Akililu, Yemisirach B.; Bouffet, Eric; Abebe, Mersha (Frontiers in Oncology, 2025)
BackgroundMedulloblastoma is the most common malignant central nervous system tumor in pediatric patients and is relatively rare in adults. Despite remarkable improvement in survival over recent decades, the high success rates in management documented in the Western world are not mirrored in middle- and low-income countries, due to various socio-economic factors and health-care disparities.ObjectiveThe aim of this study was to assess surgical treatment outcome and prognostic factors in operated patients with medulloblastoma in Tikur Anbessa Specialized Hospital and Myungsung Christian Medical Center, the 2 largest neurosurgical units in Ethiopia.MethodsThis retrospective study involved 27 patients (21 children and 6 adolescent or young adults) who underwent surgery for medulloblastoma between January 2010 and April 2018. A structured questionnaire was used to collect patients’ data and their treatment outcomes.Resultsthe 6 months and 1-year overall survival (OS) were 41% and 29% respectively, with a median survival time of 107 days (95% CI: 49,166). Median OS was 66 days (95% CI: 27,105), with 6 months and one-year OS rate of 24% for pediatric patients. Younger age at presentation, postoperative open EVD, longer Intensive Care Unit stay, lack of radiation treatment & postoperative complications were negative predictors of outcome.ConclusionThis experience underscores the high number of undiagnosed patients with medulloblastoma in Ethiopia and the poor outcome of patients who undergo active treatment. Standardization of treatment with surgery, craniospinal irradiation ± chemotherapy yields longer survival rates in both pediatric and adult patients.